The Mediating Role of Engagement and Culture in the Relationship Between Paternalism, Organizational Identification, and Voice Behavior - Allouzi, Hala; Yucel, Recep (European Scientific Journal, ESJ, 2025)
This study investigates the mediating effects of work engagement and organizational culture on the relationships between paternalistic leadership, organizational identification, and voice behavior among managers in Jordanian shareholding industrial companies. The research population comprises 3,612 top and middle-level managers across 239 companies, as identified through data from the Jordanian Ministry of Industry and Trade. A large enterprise is defined as having 500 or more employees. Employing a stratified random sampling technique, a minimum required sample size of 347 managers was determined. Of the 400 distributed questionnaires, 347 were returned, and 318 were deemed valid for analysis, resulting in a usable response rate of 79.5%. The study applied a quantitative research design and utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS software for data analysis. The results of the study revealed several significant relationships. First, paternalistic leadership was found to have a positive and direct effect on both organizational identification and voice behavior. Additionally, cultural values demonstrated a significant and positive direct influence on organizational identification as well as on voice behavior. Similarly, work engagement exhibited a positive and direct impact on organizational identification and voice behavior. Moreover, the study identified important mediating effects. Cultural values were shown to mediate the positive relationship between paternalistic leadership and organizational identification, as well as between paternalistic leadership and voice behavior. Likewise, work engagement served as a mediator in the relationship between paternalistic leadership and both organizational identification and voice behavior, reinforcing the role of engagement in strengthening leadership outcomes.